Brachial plexus paralysis after thoracoscopic esophagectomy for esophageal cancer in the prone position: A thought-provoking case report of an unexpected complication. (2019) - Aisu, Yuki; Hori, Tomohide; Kato, Shigeru; Ando, Yasuhisa; Yasukawa, Daiki; Kimura, Yusuke; Takamatsu, Yuichi; Kitano, Taku; Kadokawa, Yoshio
Highlights: This is the first case of brachial plexus injury during thoracoscopic esophagectomy in the prone position. This paralysis is due to excessive abduction and external rotation associated with the intraoperative position. To avoid intraoperative brachial plexus injury in the prone position, thoughtful orientation of the head and right arm in a less loaded position is important. Abstract: Introduction: During prone esophagectomy, placement of a port in the third intercostal space for upper mediastinal dissection requires adequate axillary expansion. To facilitate this, the right arm is elevated cranially and simultaneously turned outward. Brachial plexus paralysis associated with esophagectomy in the prone position has not been documented. Presentation of case: A 58-year-old man diagnosed with middle intrathoracic esophageal cancer was referred to our department. Thoracoscopic esophagectomy in the prone position was performed following neoadjuvant chemotherapy. After surgery, he complained of difficulty moving his right arm. Physical examination revealed perceptual dysfunction and movement disorder in the territory of cervical spinal nerve 6. Magnetic resonance imaging indicated the injury in the right posterior cord of the brachial plexus at the costoclavicular space. Therefore, we diagnosed the patient with right brachial plexus injury caused by the intraoperative position. The postoperative course was uneventful other than the brachial plexus paralysis, and he was discharged on postoperative day 23. He underwent continuous rehabilitation as an outpatient, and the right brachial plexus paralysis had completely disappeared by 2 months after surgery. Discussion: This is the first case of brachial plexus injury during thoracoscopic esophagectomy in the prone position. In prone esophagectomy, managing the patient's position, especially the head and arm positions, is so important to avoid brachial plexus injury due to intraoperative positioning. Conclusion: The clinicians should consider managing the patient's position with anatomical familiarity to avoid brachial plexus injury due to intraoperative positioning.